2016
DOI: 10.21273/jashs03690-16
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Gene Expression Drive Accumulation of Lycopene and β-Carotene in Watermelon

Abstract: Citrullus lanatus (watermelon) is an excellent daily source of dietary lycopene and β-carotene. To investigate the transcriptional regulation of carotenoid biosynthesis genes relative to lycopene and β-carotene accumulation in watermelon fruit, six watermelon accessions with different flesh colors were examined in this study: white-fleshed PI 459074, pale-yellow-fleshed ‘Cream of Saskatchewan’, light-pink-fleshed PI 482255, orange-yellow-fleshed ‘WM-Clr-1’, and red-fleshed ‘L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…While both ClPSY1 and ClPSY2 had similar transcript profiles till 18 DAP, the ClPSY1 levels were 3.3-fold higher than that of ClPSY2 at 26 DAP and peaked at 42 DAP, which was consistent with the pattern of lycopene accumulation (Figure 4B). Based on these results and previous reports detailing lack of correlation between the ClPSY2 levels and lycopene content in watermelon of different flesh color [61], we hypothesize that ClPSY1 has a dominant role in the carotenoid biosynthetic pathway during watermelon fruit ripening.…”
Section: Carotenoid Synthesis and Accumulation In Watermelon Fruitsupporting
confidence: 75%
See 1 more Smart Citation
“…While both ClPSY1 and ClPSY2 had similar transcript profiles till 18 DAP, the ClPSY1 levels were 3.3-fold higher than that of ClPSY2 at 26 DAP and peaked at 42 DAP, which was consistent with the pattern of lycopene accumulation (Figure 4B). Based on these results and previous reports detailing lack of correlation between the ClPSY2 levels and lycopene content in watermelon of different flesh color [61], we hypothesize that ClPSY1 has a dominant role in the carotenoid biosynthetic pathway during watermelon fruit ripening.…”
Section: Carotenoid Synthesis and Accumulation In Watermelon Fruitsupporting
confidence: 75%
“…In contrast, its paralog CmPSY1 is predominantly expressed in the ripe melon fruit [28]. Wang et al [61] analyzed ClPSY2 transcripts in six watermelon cultivars with distinct fruit pigmentation and found that the expression profile of ClPSY2 was not consistent with lycopene accumulation. The red-fleshed MSW28 cultivar had the highest lycopene content, while ClPSY2 displayed lower levels.…”
Section: Discussionmentioning
confidence: 99%
“…This might indicate that the accumulation of lycopene was not dependent on the expression of LCYB . It was also likely that the difference in protein levels or functionality may regulate the color of the fruit (Wang et al, 2016). This seemed contradictory when we combined the results of QTL mapping and transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There are usually multiple PSY genes in plants, but only one has been found in Arabidopsis 26 and three in tomato and cassava 27 . Not every PSY gene is related to carotenoid accumulation in fruits, and their expression is specific 28 . In this study, three PSY genes were found, and PSY-1 and PSY-2 were upregulated under CO 2 enrichment.…”
Section: Resultsmentioning
confidence: 99%